The art of leadership and office management (Global Scientific Review, 2023)
Strategic thinking can be used in any organization seeking to gain a competitive edge. With a focus on improvement, often through creativity and innovation, strategic thinking builds a vision for an organization’s future prior to the linear process of developing a strategic plan. The literature on strategy is divided into two camps: one focuses on an organization’s strategic planning process; the other on a more holistic endeavor within the organization. In the face of the competition and change that exists in today’s market, libraries and their leadership can take advantage of strategic thinking in order to move the library forward toward a new and more successful future.